Nilai-nilai Kearifan Lokal Dalam Kesenian Tayub Agung Manggolo Laras Desa Sumberagung Kecamatan Rejotangan Kabupaten Tulungagung - Luckytasari, Voltadana; Shofa, Abd. Mu’id Aris (JPK (Jurnal Pancasila dan Kewarganegaraan), 2023)
Tayub art is one of the arts that is considered not good by most people, because there are elements that are not good in it such as drunkenness, obscenity, and other despicable acts. The purpose of this study is to describe the values of Pancasila in the local wisdom of the art of Tayub Agung Manggolo Laras, Sumberagung Village, Rejotangan District, Tulungagung Regency. This study uses a qualitative approach. Sources of data used in this research are informants, events, and documents. Data analysis used in research is in the form of data reduction, data display, and verification or conclusion. The results of the study show that the values of Pancasila in the local wisdom of Tayub Agung Manggolo Laras art are belief in God (religiosity), humanity (morality), Indonesian unity (nationality), deliberation and representation, and social justice. Recommendations for further research are the need to study more about traditional arts such as Tayub art, and research Tayub art in other areas so that the results can be compared.